2011
DOI: 10.4193/rhino10.001
|View full text |Cite
|
Sign up to set email alerts
|

Reduced olfactory bulb volume in total laryngectomy patients: a magnetic resonance imaging study

Abstract: Objectives: The olfactory bulb (OB) is a remarkably plastic structure with highly active afferent neurons, which is partly reflected by its volume. Although deterioration of olfaction after total laryngectomy is reported by many patients, this problem has not received widespread attention. There has been no study that had addresses this loss olfactory ability as a function of OB volume. The aim of this study was to determine OB volume changes after laryngectomy. Study design: Twenty one patients post-total la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…15 Many researchers have discussed the effect of various bilateral and systemic diseases on the size of OB. [3][4][5][6][7][8][16][17][18][19] These cross-sectional studies indicate that: (1) OBV seems to change in parallel to smell function, (2) OBV decreases with duration of olfactory loss, and (3) patients with parosmia present with smaller OB compared with those without. The effect of treatment on OBV was investigated by Gudziol et al, 20 who found that treatment of patients with chronic rhinosinusitis is accompanied by increased OBV.…”
Section: Discussionmentioning
confidence: 73%
“…15 Many researchers have discussed the effect of various bilateral and systemic diseases on the size of OB. [3][4][5][6][7][8][16][17][18][19] These cross-sectional studies indicate that: (1) OBV seems to change in parallel to smell function, (2) OBV decreases with duration of olfactory loss, and (3) patients with parosmia present with smaller OB compared with those without. The effect of treatment on OBV was investigated by Gudziol et al, 20 who found that treatment of patients with chronic rhinosinusitis is accompanied by increased OBV.…”
Section: Discussionmentioning
confidence: 73%
“…Due to tracheostomy performed after total laryngectomy, the nasal airway is interrupted, and the neuroepithelium specialized for olfaction is deprived of odor particles. 6 Two mechanisms potentially explaining olfactory loss after laryngectomy are interruption of nasal airflow after laryngectomy and impairment of neurosensory feedback mechanisms after multiple peripheral nerve injuries during surgery. 5 The OB displays plasticity throughout adult life, based on two major neurobiological mechanisms; one is related to the continuity of neurogenesis from the subventricular zone, and the other is related to the continuity of synaptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“… 1 OB volumes measured postoperatively in laryngectomized patients were reported to be lower than those in a similar age control group. 5 , 6 Atrophy of the olfactory neuroepithelium or the OB may play a role in the emergence of olfactory problems in patients after laryngectomy. 6 , 18 , 19 , 21…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations